Effects of age group and oil type supplementation on fat deposition in kacang goats - Karami, Morteza; Alimon, Abdul Razak; Sazili, Awis Qurni; Goh, Yong Meng (2009)
Commercial Kacang goat breed (n = 32) were used in a completely randomized design with 2 x 2 factorial experiment to determine the effects source of oil (Palm and Canola oil) in different ages, 4-8 month (Group A) and 8-12 month (Group B) and interaction between Age and Oil on carcass internal fat characteristics of kids. Rations were total mix ratio (TMR) with isometabolizable energy and isonitrogenous. Feedlot period was 16 weeks (2 weeks adaptation and 14 weeks fattening). The average initial and final weight were 13 kg and 22.24 kg that between different age and two kind of oil had not significant. Mean of daily weight gain was 92.43 g/d. Warm carcass weight in group A was lower than group B and dressing percentage in group A was higher than group B, but had not significant (P>0.05). The mean of dressing percentage was 47.86 percent and dressing percentage of group A was higher than other groups but had not significant. Mean of kidney fat weight in canola oil was (156.1) lower than palm oil (215.5), had significant (p<0.05). In interaction between oil in age group, kidney fat weight in canola oil was lower than palm oil in group A and B, that different between them were significant (p<0.05). In conclusion, in different age and oil carcass weight, dressing percentage and internal fat except kidney fat (p<0.05) were same but in group A, effect of canola oil was better than other oil and in group B palm oil was efficient than canola oil, of coarse they had not significant (p>0.05).